The phenomenon of abnormal eating and taste perception: What's the link in subjects with obesity and eating disorders?. (March 2023) - Cattaneo, Camilla; Mambrini, Sara Paola; Gilardini, Luisa; Scacchi, Massimo; Castelnuovo, Gianluca; Pagliarini, Ella; Bertoli, Simona
Highlights: The relationship between taste perception and eating disorders was investigated. Taste impairments occurred differently in obese subjects with eating disorders. Subjects with mixed eating disorders shown a reduced perception of salty stimuli. Emotional and external eating characterized obese with eating disorders. Targeting taste might be a promising strategy to personalize the dietary approach. Abstract: Eating disorders (i.e., food addiction and binge eating) are a significant cause of morbidity and mortality and are considered one of the most common underlying causes of weight loss failure. Despite ongoing efforts to better understand dysregulated eating, the core phenomenon of the mechanisms underlying the perception of food properties and the possible sensory deficits in eating disorders remains scarcely investigated. This is surprising as the perception of food plays a central role in choosing what we eat and could be relevant in maintaining disordered eating behaviours in patients with obesity. To address this knowledge gap, we tested the hypothesis that taste response profiles are differentially linked to nutritional status and eating disorder types. In addition, a range of eating behavioural attitudes associated with over-consumption was also evaluated to assess their importance in driving abnormal eating. One hundred and twenty-two patients with obesity were studied (37 simple obese; 43 obese with food addiction; 42 obese with co-occurring food addiction and binge eating). Forty-three subjects were recruited as the control group. Sweet and salty taste thresholds (target stimuli associated with binge/compulsive eating) were measured with the 3-Alternative-Forced-Choice method, and eating habits (external, emotional, and restrained eating) were assessed by the Dutch Eating Behaviour Questionnaire. Results generally showed that patients with obesity (with and without eating disorders) presented a significantly (p < 0.001) lower acuity to sweet and salty tastes compared to controls. In particular, patients with co-occurring food addiction and binge eating showed the highest salty threshold compared to the other groups. Moreover, this group had significantly (p < 0.001) higher emotional and external eating scores than the others. Our data suggest that targeting taste might be a novel approach toward weight control to prevent the risk of therapeutic failure, identify new intervention strategies and, above all, personalise the type of dietary approach to be adopted with the obesity endophenotype.